IMPACT OF PSYCHOLOGICAL HEALTH ON ACADEMIC PERFORMANCE OF MEDICAL STUDENTS. WHERE DO WE STAND? - Hamna Khan; Ain ul Momina; Muhammad Zeeshan Sarwar (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: The objective of our study is to evaluate the prevalence of anxiety, stress and depression in undergraduate MBBS students to correlate it with self-efficacy, life satisfaction and to evaluate its effect on academic performance. We have also considered the relation between academic year and last year score. METHODOLOGY: A total of 800 self-administered questionnaires were filled by 1st year to final year undergraduate students using non-probability, purposive sampling. The 10-minute questionnaire comprised of four sections: (1) demographics (2) Depression, Stress and Anxiety Scale (DASS ) 21 scoring system (3) Satisfaction with Life Scale (4) General Self-Efficacy Scale. The demographic questions included participants’ age, gender, and year of study, residence and last year professional examination score percentage. A percentage below 50% was named as low achievers. A percentage from 50% to 70% was considered as moderate achievers and above 70% as high achievers. RESULTS: In this sample of 505 students 180 (35.6%) were male undergraduates consisting of 18.6% from 1st year, 26.5% from 2nd year and 20.8%, 18% and 16% from 3rd year, 4th year and final year respectively. The depression, anxiety and stress rate were 69.5%, 78.6% and 63.4% respectively. Generally, depression, anxiety and stress were found more in females as compared to males. Anxiety was more common as compared to stress and depression. Students of 4th year were experiencing least psychological stress. CONCLUSION: Moderate level of depression, stress and anxiety is necessary for good grades but excess of these psychological problems leads to emotional exhaustion and has a negative effect on learning and academic score. These psychological problems also lower the general self-efficacy of a student and are associated with low satisfaction with life.